972 Investigating the Modified Glasgow Prognostic Score as A Tool in Patients Undergoing Surgery for Sarcoma - A Newcastle Cohort Study. (12th October 2021) - Chan, C; Rankin, K
Abstract: Aim: Sarcomas are an aggressive group of cancers with a poor prognosis. The modified Glasgow Prognostic Score (mGPS) uses CRP and albumin levels to generate a score from 0 to 2. A higher mGPS is associated with worse outcomes and is validated in various carcinomas. However, less evidence exists for its usefulness in sarcoma and this study aims to further investigate this area. Method: All patients with a bone or soft tissue sarcoma diagnosis presenting to the North of England Bone and Soft Tissue Tumour Service between 2010 – 2014 were analysed. A retrospective review of clinical notes, pre-operative biochemistry results and oncological outcome was performed. Primary outcome measures were local recurrence or metastasis and overall survival (OS). Results: 80 patients met the inclusion criteria (28 females and 52 males). 64% of patients were aged >50 at diagnosis. 78% of tumours were high grade (Trojani Grade 2/3) and 71% were >5cm in size. 51 patients had a calculated mGPS=0, 19 patients had mGPS=1 and 10 patients had mGPS=2. In the mGPS=0 group, 22% developed recurrence or metastases and median OS was 42.2 months. For an mGPS of 1 and 2, the rate of recurrence or metastasis was 58% and 60% respectively, and median OS was 41.6 and 39.9 months. Conclusions: Pre-surgical CRP and albumin levels (mGPS) may be important in predicting outcome and aiding the management of sarcoma patients. In this cohort, a higher mGPS (1/2) was associated with increased frequency of recurrence or metastasis, however further data is required to determine statistical significance.